2014
DOI: 10.7554/elife.04147
|View full text |Cite
|
Sign up to set email alerts
|

Decoding odor quality and intensity in the Drosophila brain

Abstract: To internally reflect the sensory environment, animals create neural maps encoding the external stimulus space. From that primary neural code relevant information has to be extracted for accurate navigation. We analyzed how different odor features such as hedonic valence and intensity are functionally integrated in the lateral horn (LH) of the vinegar fly, Drosophila melanogaster. We characterized an olfactory-processing pathway, comprised of inhibitory projection neurons (iPNs) that target the LH exclusively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
209
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(235 citation statements)
references
References 69 publications
25
209
1
Order By: Relevance
“…In line with this, previous data from fly larvae suggested that a set of odor-responsive dopaminergic neurons projecting to the LH increased attraction to appetitive odors during hunger [39]. In addition, in the adult fly, the LH appears segregated into regions for innately appetitive and aversive odors as judged by inhibitory PN innervation and activation [40]. Thus, hunger could decrease the output of the avoidance zone and thereby avoidance behavior.…”
Section: Context-dependent Parallel Processing Of Comentioning
confidence: 68%
“…In line with this, previous data from fly larvae suggested that a set of odor-responsive dopaminergic neurons projecting to the LH increased attraction to appetitive odors during hunger [39]. In addition, in the adult fly, the LH appears segregated into regions for innately appetitive and aversive odors as judged by inhibitory PN innervation and activation [40]. Thus, hunger could decrease the output of the avoidance zone and thereby avoidance behavior.…”
Section: Context-dependent Parallel Processing Of Comentioning
confidence: 68%
“…In addition, the targeting patterns of the two PN populations within the LH were distinct, with projections from DA1 terminating in the ventral LH and those from DM1 terminating more dorsally (Figure 2A and 2B). These projection patterns are in agreement with the literature (Jefferis et al ., 2007; Strutz et al ., 2014). Finally, while we observed postsynaptic signal from both DA1 and DM1 throughout the AL, the signal distribution was not homogeneous and was different between the two.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we are unable to attribute this smaller relative calyx volume to changes in modality-specific subunits and must consider calyx volume as a whole. Interestingly, the lateral horn, which is more important for naive odor preferences [Parnas et al, 2013;Strutz et al, 2014], remained constant in relative volume. This suggests that smaller individuals (with a relatively smaller calyx) rely more on naive than on learned behavior.…”
Section: Groothuis/smidmentioning
confidence: 97%